A history of the Chinese language - Dong, Hongyuan, 1976- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"A History of the Chinese Language provides a comprehensive introduction to the historical development of the Chinese language from its Proto-Sino-Tibetan roots in prehistoric times to Modern Standard Chinese. Taking a highly accessible and balanced approach, it presents a chronological survey of the various stages of the Chinese language, covering key aspects such as phonology, syntax and semantics. The second edition presents a revised and updated version that reflects recent scholarship in Chinese historical linguistics and new developments in related disciplines. Features include: Coverage of the major historical stages in Chinese language development, such as Old Chinese, Middle Chinese, Early Modern Chinese, and Modern Standard Chinese. Treatment of core linguistic aspects of the Chinese language including phonological changes, grammatical development, lexical evolution, vernacular writing, the Chinese writing system and Chinese dialects. Inclusion of authentic Chinese texts throughout the book, presented within a rigorous framework of linguistic analysis to help students to build up critical and evaluative skills and acquire valuable cultural knowledge. Integration of materials from different disciplines, such as archaeology, genetics, history and sociolinguistics, to highlight the cultural and social background of each period of the language. Written by a highly experienced instructor, A History of the Chinese Language will be an essential resource for students of Chinese Language and Linguistics and for anyone interested in the history and culture of China"--
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- History; Language and culture -- China; Historical linguistics -- China; China -- Languages -- History; LANGUAGE ARTS & DISCIPLINES / Journalism